Cognitive, social, and neural determinants of diminished decision-making and financial exploitation risk in aging and dementia: A review and new model. Issue 4 (19th October 2016) - Spreng, R. Nathan; Karlawish, Jason; Marson, Daniel C.
ABSTRACT: In this article we will briefly review how changes in brain and in cognitive and social functioning, across the spectrum from normal to pathological aging, can lead to decision-making impairments that increase abuse risk in many life domains (e.g., health care, social engagement, financial management). The review will specifically focus on emerging research identifying neural, cognitive, and social markers of declining financial decision-making capacity in older adults. We will highlight how these findings are opening avenues for early detection and new interventions to reduce exploitation risk.